Social facilitation within immersive virtual reality enhances perseverance in stroke rehabilitation training - Hadjipanayi, Christos; Sokratous, Dimitris; Kyrlitsias, Christos; Banakou, Domna; Michael-Grigoriou, Despina (My University, 2025)
Introduction: Integrating social interaction into stroke rehabilitation is recommended but often underutilized due to limited resources. Virtual Reality (VR) offers a way to introduce social facilitation via virtual agents in rehabilitation training. Understanding how chronic stroke survivors respond to virtual agents can inform physiotherapy practice with innovative digital tools. Methods: This study presents five case studies of chronic stroke survivors (2 female, 3 male) with motor impairments, all with paresis of the dominant right upper limb. Participants engaged in a VR-based upper limb exergame under two conditions: playing alone and playing alongside with a virtual agent, acting as a second-player, controlled by a rule-based algorithm. Rehabilitation progress, task performance, and engagement were examined across training sessions. Results: Participants who completed all sessions showed consistently higher engagement when playing with a virtual agent compared to playing alone. At the same time, the presence of the virtual co-player had no observable effect on game performance. Discussion: These findings suggest that incorporating a virtual agent can enhance task engagement and promote perseverance in VR-based stroke rehabilitation. The results are discussed in the context of current VR rehabilitation practices, and implications for clinical practice and future research are outlined.
Keywords: virtual reality; rehabilitation; stroke; social facilitation; co-presence; virtual agents